Plagiarism: in the lense of undergraduate students Universiti Teknologi MARA (UiTM) Johor - Osman, Suhaila; Mohd Noor, Jannah Munirah; Ahmad, Rohayu; Mohammed, Nor Rashidah; Mat Yatim, Nurul Huda (2013)
Pertaining to the dumper sources of information available nowadays, the use of information are inquisitive as some of the students might not realize that they have committed plagiarism and some of them do not aware what plagiarism is about. There is no doubt that the sources of information in this age are known as one of the important factors towards the excellencies of students in completing their assignment. However, the issue arises here is does those students used it in the actual way in performing their task? The purposes of this study are to look for the perception of the undergraduate students in Universiti Teknologi MARA (UiTM) Johor regarding the plagiarism activities and their experiences. The studies on plagiarism among university students have been recognized as an interesting area of study in the academic world and it is important. A study done by Nitterhouse (2003), quoted from McCabe and Trevino (1996), found that the number of students who committed plagiarism increased at university. They added that the plagiarism recently seems to be widespread and growth rapidly among the undergraduate students and the research found that the plagiarism activities were done by more than half of the undergraduates. Due to this problem, the objectives of this study are; to find out the level of awareness among Undergraduate Students in plagiarism, to determine the Undergraduate Students knowledge on the sources of information and also to investigate the possible factors that contribute to the plagiarism activities. Taking this view into consideration, a study was conducted amongst Undergraduate Students in UiTM Johor. This study used quantitative method and 5 percent of the respondents are from three different faculties, which are Faculty of Accounting, Faculty of Business Management, and Faculty of Information Management were involved as well. This study used questionnaires as the instruments and those questionnaires were distributed to the selected class. The findings of the study indicate that plagiarism do exist in UiTM Johor and this study proposes some recommendations and changes in the mean of minimizing the numbers of plagiarism